Secreted aspartyl proteinase (PbSap) contributes to the virulence of Paracoccidioides brasiliensis infection. - Daniele Gonçalves Castilho; Alison Felipe Alencar Chaves; Marina Valente Navarro; Palloma Mendes Conceição; Karen Spadari Ferreira; Luiz Severino da Silva; Patricia Xander; Wagner Luiz Batista (Public Library of Science (PLoS), 2018)
Paracoccidioidomycosis (PCM) is the most prevalent deep mycosis in Latin America and is caused by fungi from the Paracoccidioides genus. Virulence factors are important fungal characteristics that support the development of disease. Aspartyl proteases (Saps) are virulence factors in many human fungal pathogens that play an important role in the host invasion process. We report here that immunization with recombinant Sap from Paracoccidioides brasiliensis (rPbSap) imparted a protective effect in an experimental PCM model. The rPbSap-immunized mice had decreased fungal loads, and their lung parenchyma were notably preserved. An aspartyl protease inhibitor (pepstatin A) significantly decreased pulmonary injury and reduced fungal loads in the lung. Additionally, we observed that pepstatin A enhanced the fungicidal and phagocytic profile of macrophages against P. brasiliensis. Furthermore, PbSAP expression was highly altered by environmental conditions, including thermal stress, dimorphism switching and low pH. Hence, our data suggest that PbSap is an important virulence regulator in P. brasiliensis.